Mechanical characterization of composites prepared from WC powders coated with Ni rich binders - Fernandes, C. M. (2008)
In this study composite powders of WC and Ni/Fe/Cr were prepared in an innovative way, which consists of the sputter-deposition of the metallic binder onto the tungsten carbide particles. Compacts of coated powders were sintered by conventional vacuum sintering followed by hot isostatic pressing (HIP) to reach almost full densities. In order to evaluate the mechanical properties of reduced specimens size (microcomponents), depth-sensing indentation equipment was used. This method enabled the evaluation of the hardness, H, Young's modulus, E, and the yield stress, [sigma]y, in a non-destructive way, using only one sample. For the composites of sputter-coated WC-Ni/Fe/Cr the results showed an effective reduction of H and E due to the properties of Ni and the binder characteristics of the coated powders, such as uniform distribution and nanometer structure.